1990
DOI: 10.1016/s0006-3495(90)82573-x
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer adsorption of lysozyme on a hydrophobic substrate

Abstract: Macromolecular adsorption is known to occur as a complex process, often in a series of steps. Several models are discussed in the literature which describe the microscopic structure of the adsorbate. In the present study we investigated the adsorption of hen egg white lysozyme on alkylated silicon oxide surfaces. A combination of fluorescence excitation in the evanescent field and fluorescence recovery after photobleaching allowed us to measure the amount of adsorbed fluorescent lysozyme and the equilibrium ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 23 publications
(23 reference statements)
3
40
0
Order By: Relevance
“…The HEWL adsorbed amount continued to increase even after 24 h where the adsorbed amount was greater than that predicted for monolayer coverage. This is in agreement with the data of (Schmidt et al, 1990), who found that HEWL formed multilayers on alkylated silicon oxide surfaces. RNase A clearly reached a plateau in less than 30 min, and no further increase in adsorbed protein was detected.…”
Section: Resultssupporting
confidence: 93%
“…The HEWL adsorbed amount continued to increase even after 24 h where the adsorbed amount was greater than that predicted for monolayer coverage. This is in agreement with the data of (Schmidt et al, 1990), who found that HEWL formed multilayers on alkylated silicon oxide surfaces. RNase A clearly reached a plateau in less than 30 min, and no further increase in adsorbed protein was detected.…”
Section: Resultssupporting
confidence: 93%
“…However, as we previously mentioned, calibration of TIRFM can be achieved by other methods. [14][15][16] Our data on protein adsorption to glass illustrate the utility of FM in surface analysis. In addition to measuring the average amount of bound protein, we observed protein clustering.…”
Section: Discussionmentioning
confidence: 90%
“…Evaporation of a fluorescent solution on the surface 13 does not guarantee preservation of the quantum yield. In TIRFM 5 calibration methods were developed, [14][15][16] but these methods cannot be extended to conventional microscopy. These and some other methods were previously reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that in this seemingly simple system there are numerous complications, since this protein has been reported to display a side-on to end-on transition (65), conformational changes on adsorption (68), pH-dependent interfacial aggregation (67), and concentration-dependent multilayer adsorption (64 -66). In relation to the latter it is interesting to note that there seem to be large differences in the state of adsorption for early and late adsorbing proteins, since the former are poorly exchangable, whereas the latter are more extensively exchangable (69,70). Interestingly, this is coupled to a large loss in enzymatic activity for the initially adsorbing proteins, whereas the enzymatic activity of the proteins adsorbing later in the adsorption process display an effectively higher activity (69).…”
Section: "Particle-like" Proteinsmentioning
confidence: 99%
“…In relation to the latter it is interesting to note that there seem to be large differences in the state of adsorption for early and late adsorbing proteins, since the former are poorly exchangable, whereas the latter are more extensively exchangable (69,70). Interestingly, this is coupled to a large loss in enzymatic activity for the initially adsorbing proteins, whereas the enzymatic activity of the proteins adsorbing later in the adsorption process display an effectively higher activity (69). It is interesting to note that the readily exchangable fraction increases and the irreversibly adsorbed fraction decreases with an increasing bulk protein concentration (70).…”
Section: "Particle-like" Proteinsmentioning
confidence: 99%